BIOS-01. MANAGEMENT OF OPTIC PATHWAY GLIOMA: A SYSTEMATIC REVIEW AND META-ANALYSIS. (14th November 2022) - Yousefi, Omid; Azami, Pouria; Sabahi, Mohammadmahdi; Adada, Badih; Borghei-Razavi, Hamid
Abstract: In the current study, we systematically review the literature regarding the management of optic pathway glioma (OPG). This review will analyze demographics, information regarding the type of treatment, radiological and clinical (visual) outcomes, and also complications. Article selection was performed by searching PubMed, Web of Science, and Cochrane databases. Of the 105 eligible studies, a total of 4177 patients underwent different therapeutic modalities including surgery, radiotherapy, and chemotherapy. The mean age was 8.17 years and the gender ratio was 97 males per 100 females. Based on the available data, the mean follow-up was 98.6 months and 48.7% of the patients were known cases of the neurofibromatosis type1. According to the Dodge classification 1104, 941, and 1353 tumors were D1, D2, and D3, respectively. The toxicity induced by either chemo- or radiotherapy was the most common complication, followed by the ophthalmologic complications rather than visual acuity exacerbation. The pooled mortality rate was 0.12 (95%CI 0.09–0.14). Due to the unrepresentative data, improved and not changed outcomes were classified as the favorable outcome and worsened as an unfavorable. Meta-analyses were performed to determine the rate of clinical and radiological favorable outcomes. In terms of visual assessment, the pooled rate of a favorable outcome in chemotherapy, radiotherapy, and surgery was 0.74, 0.81, and 0.65, respectively and the overall pooled rate of the favorable outcome is 0.75 (95%CI 0.70–0.80). In terms of radiological assessment, the rate of a favorable outcome following chemotherapy, radiotherapy, and surgery was 0.71, 0.74, and 0.67, respectively and the overall pooled rate of the favorable outcome is 0.71 (95%CI 0.65–0.76). The subgroup analysis revealed no significant difference in the rate of clinical and radiological favorable outcomes between the different treatment modalities (P > 0.05). Our analyses showed that each therapeutic modality represents viable treatment options to achieve remission for these patients.